Effects of transformation-induced plasticity on the small-scale deformation behavior of single crystalline complex concentrated alloys. (February 2020) - Choi, Won Seok; Oh, Hyun Seok; Lai, Minjie; Malyar, Nataliya V.; Kirchlechner, Christoph; Park, Eun Soo; Choi, Pyuck-Pa
Abstract: We study the effects of transformation-induced plasticity (TRIP) on the micrometer-scale deformation of single crystalline pillars. Plastic deformation mechanisms (i) mediated by pure dislocation glide and (ii) strain-induced epsilon-martensite transformation are separated using compositionally complex model alloys. The results show that transformation-induced plasticity does not strengthen the single crystalline material at the micron-scale when loaded in uniaxial compression as compared to pure dislocation-mediated plasticity. The dynamically introduced phase boundaries effectively hinder the activation and propagation of secondary slip systems, resulting in no increase in local stress due to unobstructed slip on the primary slip system parallel to the phase boundary. Graphical abstract: Image, graphical abstract